PERAN DAN TANGGUNG JAWAB PENGURUS DALAM PROSES PKPU (STUDI PUTUSAN PENGADILAN NEGERI SURABAYA NOMOR 70/PDT.SUS-PKPU/2021/PN.NIAGA.SBY) - Muhammad Ferdi Hamzah (2022)
Companies in general in carrying out their business activities have a goal to achieve maximum profit. However, sometimes the company experiences financial problems such as the amount of company debt, resulting in the company's bankruptcy. With events like that, many parties are harmed such as creditors, employees, etc. To be able to overcome the company's financial problems, one can go through legal channels, one way is through the Suspension of Debt Payment Obligations or PKPU. According to Munir Fuady, PKPU is a period given by law to debtors through a commercial judge's decision, in which creditors and debtors are given the opportunity to discuss ways to pay their debts and give all or part of their debts. The requirement for submitting a PKPU application is that there are 2 creditors whose debts have matured. In handling the PKPU application, the Panel of Judges appoints the Supervisory Judge and appoints 2 Managements as people who have the task of managing the debtor's assets. Management must be independent and have no interest in creditors or debtors. The role of the Management is needed to supervise and manage the debtor's assets, if the debtor harms the creditor, the Management can take actions that can save the debtor's assets. And the Management still has responsibility after PKPU is declared homologated. Keywords: Bankruptcy, PKPU, Management, Creditor, Debtor